Systematic review: use of the BIM concept in projects of the electricity sector over the (Inter)National scenarios (Research, Society and Development, 2022)
The BIM is a project management concept widely used in the new methodologies of the AECO areas, this involves adaptation of the most modern resources in computational technologies, implying digital design and best practices in project operation, whatever phases it applies to. Even though the BIM widespread at AECO, it is speculated the concept is still little adopted in projects in the electric energy sector. By forming an evident interest in the adoption of BIM in the electric sector, this work has intended to highlight this discussion, adopting a strategy based on the evaluation of academic research proposals aimed at adopting the concept in projects in the electricity sector, involving a (Inter)National context. To this intent, the work aims to provide the reader with a basic understanding of the BIM concept; and next, carry out a systematic review of the academic literature on the use of BIM in the electricity sector, by solving a methodology of search, selection, and inclusion of the materials leading them to the research data, which have to be classified on the level of maturity in use of BIM, while analysis activities provide evidence and discussion on the data. However, with the performance of analysis activities on some modeling of the review data, it was possible to highlight situations in the evaluated period. It was about the use of BIM in the electric sector involving information on nationality and recent chronology, even in addition to other attributes inherent to the data of the study.